Manajemen Krisis Dinas Kesehatan Kota Bandung untuk Mengembalikan Kepercayaan Publik Terhadap Vaksin Covid-19 - Rifqi Siswadi, Ilyasa Mochammad; Wibawa, Darajat; Mukhtar, Khoiruddin (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This research was conducted to find out how the implementation of crisis management carried out by the Bandung City Health Office in an effort to restore public trust in the covid-19 vaccine by referring to the four-step concept of Public Relations proposed by Cutlip, Center, and Broom, which consists of fact finding in the field (fact finding), planning and programming (planning and programming), carrying out action and communication (taking action and communication), and evaluating (evaluating). This research was conducted using a qualitative approach, and the research method used was a descriptive method. In addition, this research was conducted using the paradigm of constructivism, and data collection techniques by means of observation and interviews. Based on the results of research that can be concluded that crisis management in an effort to restore public confidence in the covid-19 vaccine goes through several stages, namely the first is the planning stage of handling negative issues, the second is the dissemination of information about the covid-19 vaccine, the third is to take into account success indicators.